2005
DOI: 10.1115/1.2181596
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Diesel Spray Flame Liftoff, Sooting Tendency, and NOx Emissions Using Detailed Chemistry With Phenomenological Soot Model

Abstract: A detailed chemistry-based CFD model was developed to simulate the diesel spray combustion and emission process. A reaction mechanism of n-heptane is coupled with a reduced NOx mechanism to simulate diesel fuel oxidation and NOx formation. The soot emission process is simulated by a phenomenological soot model that uses a competing formation and oxidation rate formulation. The model is applied to predict the diesel spray lift-off length and its sooting tendency under high temperature and pressure conditions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(78 citation statements)
references
References 18 publications
4
74
0
Order By: Relevance
“…76 Research has shown that the composition and morphology of soot/particulate matter emissions from LTC strategies can vary widely, [78][79][80][81] and it has also been shown that the two-step soot model requires significant tuning to achieve predictions over a range of combustion modes. 82 Therefore, in this study, the qualitative sooting tendency of a given combustion strategy will be discussed using local equivalence ratio versus local temperature diagrams, like the one shown in Figure 1.…”
Section: Multi-dimensional Cfd Engine Modelingmentioning
confidence: 99%
“…76 Research has shown that the composition and morphology of soot/particulate matter emissions from LTC strategies can vary widely, [78][79][80][81] and it has also been shown that the two-step soot model requires significant tuning to achieve predictions over a range of combustion modes. 82 Therefore, in this study, the qualitative sooting tendency of a given combustion strategy will be discussed using local equivalence ratio versus local temperature diagrams, like the one shown in Figure 1.…”
Section: Multi-dimensional Cfd Engine Modelingmentioning
confidence: 99%
“…The third CFD results in the iteration were compared with the experimental results. Although a Primary Reference Fuel (PFR) blend of 71% (by volume) n-heptane and 29% (by volume) iso-octane, or PFR29, was used in the experiment, 100% n-heptane chemical reaction kinetics and fuel properties were used in the model prediction due to the availability of a chemistry mechanism (11) .…”
Section: Resultsmentioning
confidence: 99%
“…For the prediction of the temperature distribution of the engine components, such as the piston, liner, and cylinder head, a finite element Heat Conduction in Components (HCC) code (5) was used. (6) GASJET model (7) Radiation Discrete Ordinates Method (DOM) (8) Soot Refractive index m = n -κ i =1.8-1.0 i (9) Hot gas wide-band gray approximation (10) Combustion Detailed chemistry mechanism (11) Improved n-heptane reaction mechanism (12) Soot formation Two-step model (11) NO x Improved reduced 19-step model (13) Turbulence RNG k-ε Wall temperature Heat Conduction in Components code (5) The Discrete Ordinates Method (DOM) solves the Radiation Transfer Equation (RTE) for the intensity of radiation in a set of ordinates, each weighted by the solid angle subtended by that ordinate. The RTE and its boundary conditions are (14,8) …”
Section: Numerical Modelsmentioning
confidence: 99%
“…For spark-ignition engines, knock occurrence, which limits the compression ratio and therefore the efficiency at which a spark-ignition can operate, has been investigated with the use of numerical modeling and chemical models [Liang, L., Reitz, R., Iyer, C., and Yi, 2007;Linse, Kleemann, & Hasse, 2014]. The relationship of soot and nitrogen oxide (NOx) formation with various conditions within a diesel engine such as temperature, pressure and flame lift-off length, as well as design parameters such as spray nozzle geometry has also been explored using chemical kinetics [Kong, Sun, & Rietz, 2007;Som, Ramirez, Longman, & Aggarwal, 2011]. There exist numerous other studies in the literature that utilized chemical kinetic models to predict engine performance.…”
Section: Applicationsmentioning
confidence: 99%